1968
DOI: 10.1002/jbm.820020406
|View full text |Cite
|
Sign up to set email alerts
|

In vitro testing of silicone rubber heart‐valve poppets for lipid absorption

Abstract: SummaryAn in vitro procedure for measuring the affinity of silicone rubber balls forThe method appears to duplicate weight and volume inPotential lipid absorption is shown to inlipid is described. creases occasionally noted in vivo. crease with degree of cure, and decrease with filler content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In addition, silicone devices have been shown to fail in longterm implants, particularly in flex-fatigue applications such as finger joints2' and heart valve poppets. 22 The mechanism of in vivo degradation is not clear. Chan et al23 studied the exchange of Si-0 groups with P-0 groups that are found in some nucleic acids and phosphates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silicone devices have been shown to fail in longterm implants, particularly in flex-fatigue applications such as finger joints2' and heart valve poppets. 22 The mechanism of in vivo degradation is not clear. Chan et al23 studied the exchange of Si-0 groups with P-0 groups that are found in some nucleic acids and phosphates.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of silicone rubber balls used as mitral-valve poppets some changes can occur, namely discoloration, weight gain, swelling, wear and splitting in a small percentage [2,3]. The probable reason for all these changes is lipid absorption [2,3], particularly as Carmen and Kahn [4,5] have duplicated the effect in vitro. Conceivably such absorption could contribute to mechanical failure, as chemical deterioration of the surface is known to be a prime initiator of stress corrosion and corrosion fatigue failures of polymers [ 6 ] .…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, it is likely that the epileptogen in these cases was not DMPSO itselfbut a pyrolysis product of DMPSO which was extracted from the overcured membrane during perfusion. Indeed, it has been demonstrated that the extractable content of DMPSO rubber increases as it is overcured (Carmen and Kahn, 1969), although the byproducts formed by such overcuring have not been characterized.…”
Section: Discussionmentioning
confidence: 99%